STUDI KEPUASAN PELANGGAN TERHADAP KINERJA JASA LAYANAN PDAM DENGAN METODE IMPORTANCE PERFORMANCE ANALYSIS - Dion Achmad Armadi; Hendro Sasongko; Doni Wihartika (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2019)
Customer satisfaction, emotional bonding, trust, choice reduction and habit, too history with company is a key factor for convince the customer to use product and services continue, the other factors can make customers become loyal to the quality of products and promotions. This study aims to measure the performance of services provided by regional companies such as PDAM to the community, the level of customer satisfaction is a reflection of the company's performance, a measurable data is needed that is taken directly to customers. With the help of the Importance Performance Analysis method, performance can be measured and easily understood by decision makers. So that poor performance can be seen and anticipated for future needs. Customer satisfaction of PDAM reaches 74.49% with the main priority that needs to be improved from the services provided are the ability of Social Media Admin Website Officers with performance indicator values of 2.93 and importance indicator values of 3.10. (D.Quadrant Concentrate Here).